Perception of managerial staff and workers on labour motivation and timing of operation factors in agriculture productivity in Libya - Ahmad, Ahnaish Muftah (2014)
This study considered the most important factors determining the success of any agricultural projects. These include planning; follow up, job satisfaction, organisation environment, training and scheduling. The major problems in this study are low productivity in agricultural projects due to low performance. The objectives of the study are (i) to determine the perspective of workers on labour motivation and timing of operations factors in agricultural projects in Libya. (ii) to study the perspective of managerial and supervisors on labour motivation and timing of operations factors in agricultural projects in Libya. (iii) to analyse the relationship between the elements in labour motivation and timing of operations in this study. (iv) to develop the agricultural projects productivity framework in Libya. Meanwhile, the research method used consists of secondary information through library study and primary data collected through questionnaire. The study had chosen five agricultural projects in Libya to conduct this research. The total collected sample size was 231 participants, 52 of them were managers and supervisors, and 179 workers. Two sets of questionnaire were used, the first includes 59 questions for the managers and supervisors and the second includes 35 questions for workers and staff. The results obtained from the reliability test, arithmetic mean, standard deviation and percentages showed that the biggest problem was the follow-up factor followed bytraining factor, in addition to the weakness was evident in other factors. Finally, the findings of this study suggests that these factors (job satisfaction, organisation environment, training, planning, scheduling and follow up), should be improved in order to increase the efficiency and the performance of Libyan agricultural projects, which will lead to increasing agricultural production.